Effect of Plasmodium falciparum sulfadoxine-pyrimethamine resistance on the effectiveness of intermittent preventive therapy for malaria in pregnancy in Africa: a systematic review and meta-analysis. Issue 5 (May 2019) - van Eijk, Anna Maria; Larsen, David A; Kayentao, Kassoum; Koshy, Gibby; Slaughter, Douglas E C; Roper, Cally; Okell, Lucy C; Desai, Meghna; Gutman, Julie; Khairallah, Carole; Rogerson, Stephen J; Hopkins Sibley, Carol; et al.
Summary: Background: Resistance of Plasmodium falciparum to sulfadoxine-pyrimethamine threatens the antimalarial effectiveness of intermittent preventive treatment during pregnancy (IPTp) in sub-Saharan Africa. We aimed to assess the associations between markers of sulfadoxine-pyrimethamine resistance in P falciparum and the effectiveness of sulfadoxine-pyrimethamine IPTp for malaria-associated outcomes. Methods: For this systematic review and meta-analysis, we searched databases (from Jan 1, 1990 to March 1, 2018) for clinical studies (aggregated data) or surveys (individual participant data) that reported data on low birthweight (primary outcome) and malaria by sulfadoxine-pyrimethamine IPTp dose, and for studies that reported on molecular markers of sulfadoxine-pyrimethamine resistance. Studies that involved only HIV-infected women or combined interventions were excluded. We did a random-effects meta-analysis (clinical studies) or multivariate log-binomial regression (surveys) to obtain summarised dose-response data (relative risk reduction [RRR]) and multivariate meta-regression to explore the modifying effects of sulfadoxine-pyrimethamine resistance (as indicated by Ala437Gly, Lys540Glu, and Ala581Gly substitutions in the dhps gene). This study is registered with PROSPERO, number 42016035540. Findings: Of 1097 records screened, 57 studies were included in the aggregated-data meta-analysis (including 59 457 births). The RRR for low birthweight declined with increasing prevalence of dhps Lys540Glu (ptrend =0·0060) but not Ala437Gly (ptrend =0·35). The RRR was 7% (95% CI 0 to 13) in areas of high resistance to sulfadoxine-pyrimethamine (Lys540Glu ≥90% in east and southern Africa; n=11), 21% (14 to 29) in moderate-resistance areas (Ala437Gly ≥90% [central and west Africa], or Lys540Glu ≥30% to <90% [east and southern Africa]; n=16), and 27% (21 to 33) in low-resistance areas (Ala437Gly <90% [central and west Africa], or Lys540Glu <30% [east and southern Africa]; n=30; ptrend =0·0054 [univariate], I 2 =69·5%). The overall RRR in all resistance strata was 21% (17 to 25). In the analysis of individual participant data from 13 surveys (42 394 births), sulfadoxine-pyrimethamine IPTp was associated with reduced prevalence of low birthweight in areas with a Lys540Glu prevalence of more than 90% and Ala581Gly prevalence of less than 10% (RRR 10% [7 to 12]), but not in those with an Ala581Gly prevalence of 10% or higher (pooled Ala581Gly prevalence 37% [range 29 to 46]; RRR 0·5% [–16 to 14]; 2326 births). Interpretation: The effectiveness of sulfadoxine-pyrimethamine IPTp is reduced in areas with high resistance to sulfadoxine-pyrimethamine among P falciparum parasites, but remains associated with reductions in low birthweight even in areas where dhps Lys540Glu prevalence exceeds 90% but where the sextuple-mutant parasite (harbouring the additional dhps Ala581Gly mutation) is uncommon. Therapeutic alternatives to sulfadoxine-pyrimethamine IPTp are needed in areas where the prevalence of the sextuple-mutant parasite exceeds 37%. Funding: US Centers for Disease Control and Prevention, the Malaria in Pregnancy Consortium (funded through a grant from the Bill & Melinda Gates Foundation to the Liverpool School of Tropical Medicine), Worldwide Antimalarial Resistance Network, European and Developing Countries Clinical Trials Partnership.